2018
DOI: 10.1038/s41396-018-0243-5
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive mechanisms that provide competitive advantages to marine bacteroidetes during microalgal blooms

Abstract: Polysaccharide degradation by heterotrophic microbes is a key process within Earth’s carbon cycle. Here, we use environmental proteomics and metagenomics in combination with cultivation experiments and biochemical characterizations to investigate the molecular details of in situ polysaccharide degradation mechanisms during microalgal blooms. For this, we use laminarin as a model polysaccharide. Laminarin is a ubiquitous marine storage polymer of marine microalgae and is particularly abundant during phytoplankt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 46 publications
5
105
0
2
Order By: Relevance
“…S6). These putative laminarin PULs encode glycoside hydrolases that have been previously shown to be involved in laminarin degradation by proteomics (Kabisch et al, 2014;Xing et al, 2015) and biochemical analyses (Labourel et al, 2014;Unfried et al, 2018). We therefore used laminarin degradation activity as a functionally characterized positive control.…”
Section: Growth Of the Flavobacterial Isolates On Selected Mono/ Di-amentioning
confidence: 99%
“…S6). These putative laminarin PULs encode glycoside hydrolases that have been previously shown to be involved in laminarin degradation by proteomics (Kabisch et al, 2014;Xing et al, 2015) and biochemical analyses (Labourel et al, 2014;Unfried et al, 2018). We therefore used laminarin degradation activity as a functionally characterized positive control.…”
Section: Growth Of the Flavobacterial Isolates On Selected Mono/ Di-amentioning
confidence: 99%
“…Despite its quite recent discovery in 2005 (Nedashkovskaya et al, 2005), a wide range of bioactivities of putative relevance in the cycling of matter and establishment of hostmicrobe and microbe-microbe relationships has lately been reported for a few Aquimarina strains. Besides showing a versatile carbon metabolism typical of members of the family Flavobacteriaceae and, in a broader sense, of the phylum Bacteroidetes (Alonso et al, 2007;Boone et al, 2010;Fernández-Gómez et al, 2013;Unfried et al, 2018), these organisms have been matter of current research attention owing to metabolic features of both ecological and biotechnological interest. For instance, Aquimarina salinaria (Chen et al, 2012) was shown to possess antagonistic activity towards the toxic cyanobacterium Microcystis aeruginosa (Chen et al, 2011;Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This reaction leads to glucose and the linear b1-3-glucan. Completeness of the conversion was confirmed by testing the activity of a b1-3endo glucanase of family GH17 that only cleaves undecorated, linear b1-3-glucan (Becker et al, 2017;Unfried et al, 2018) and shows little activity on the native yet high activity on the debranched laminarin. The reaction was stopped by boiling the sample for 5 min at 100°C.…”
Section: Enzymatic Preparation Of Debranched Beta-glucan From Laminarinmentioning
confidence: 99%
“…The solution was dried in vacuum overnight at 45°C to obtain a white powder. The enzymatic digestion with both enzymes and absence of glucose in the final product was recorded by high performance anionic exchange chromatography with pulsed amperometric detection (HPAEC-PAD) on a Dionex system (Unfried et al, 2018).…”
Section: Enzymatic Preparation Of Debranched Beta-glucan From Laminarinmentioning
confidence: 99%
See 1 more Smart Citation